2020
DOI: 10.33084/pedagogik.v15i1.1277
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Model Pembelajaran Direct Instruction (DI) Berbantuan Media Audiovisual Untuk Meningkatkan Hasil Belajar IPA Pada Peserta Didik Kelas V SDN-1 Langkai Palangka Raya

Abstract: Penelitian ini bertujuan untuk mendeskripsikan aktivitas belajar dan meningkatkan hasil belajar IPA menggunakan model pembelajaran Direct Instruction (DI) berbantuan media Audio Visual. Metode penelitian yang digunakan adalah penelitian tindakan kelas (PTK). Subjek penelitian kelas V sebanyak 25 orang peserta didik. Teknik pengumpulan data menggunakan observasi dan tes. Analisis data didasarkan pada hasil siklus saat proses pembelajaran. Hasil penelitian menunjukan bahwa 1) Aktivitas belajar peserta didik menj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Symbiosis learning is one of the content in science learning that is tested in the national exam. The content of science learning in symbiosis material is very important to learn, This is because science learning in symbiosis material in elementary school aims to ensure that students have the ability to provide examples of symbiosis in everyday life (Asih, 2018), develop curiosity, a positive attitude, and awareness of the mutually influencing relationship between science, the environment, technology, and society (Asysyifa et al, 2017;Septiana & Hayati, 2019;Setyawan & Riadin, 2020).…”
Section: Ntroductionmentioning
confidence: 99%
“…Symbiosis learning is one of the content in science learning that is tested in the national exam. The content of science learning in symbiosis material is very important to learn, This is because science learning in symbiosis material in elementary school aims to ensure that students have the ability to provide examples of symbiosis in everyday life (Asih, 2018), develop curiosity, a positive attitude, and awareness of the mutually influencing relationship between science, the environment, technology, and society (Asysyifa et al, 2017;Septiana & Hayati, 2019;Setyawan & Riadin, 2020).…”
Section: Ntroductionmentioning
confidence: 99%
“…4, No. 3, June 2023: 49 -53 50 less challenging for students to add new knowledge, as well as the lack of teacher knowledge in managing appropriate learning models also greatly influences student learning outcomes [13]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…In PP number 19 of 2005 article 20, it is indicated that teachers are expected to develop learning materials, which is confirmed through Permendiknas number 41 of 2007 concerning process standards, which 29 among other things regulates the planning of the learning process which requires educators in education units to develop learning resources. Thus, teachers are expected to develop learning materials as a source of learning [9]- [11]. At present, most of the learning conditions in schools are still conventional, such as the delivery of material that is only lectured.…”
Section: Introductionmentioning
confidence: 99%